1999
DOI: 10.3171/jns.1999.90.2.0306
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genetic aberrations including evidence of chromosome 11q13 rearrangement detected in pituitary adenomas by comparative genomic hybridization

Abstract: These findings indicate that genetic abnormalities are present in pituitary adenomas at a higher rate than previously reported, are associated with endocrinological activity, and often involve several chromosomes. Rearrangement at 11q13 may inactivate a tumor suppressor gene or activate an oncogene that is important in the initiation or progression of sporadic pituitary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 39 publications
1
10
0
2
Order By: Relevance
“…Our results are consistent with other CGH studies on pituitary tumors, finding chromosomes 11 and 13 to be frequent sites for genetic losses. [25][26][27] Moreover, it is known that loss of heterozygosity involving chromosomal regions 11q13 and 13q are found in 20% to 40% of sporadic pituitary tumors. 31,33,37,38 The tumor-suppressor gene for multiple endocrine neoplasia type 1 (MEN-1), an autosomal dominant cancer syndrome characterized by tumors of endocrine organs including pituitary adenomas, is located on 11q13.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with other CGH studies on pituitary tumors, finding chromosomes 11 and 13 to be frequent sites for genetic losses. [25][26][27] Moreover, it is known that loss of heterozygosity involving chromosomal regions 11q13 and 13q are found in 20% to 40% of sporadic pituitary tumors. 31,33,37,38 The tumor-suppressor gene for multiple endocrine neoplasia type 1 (MEN-1), an autosomal dominant cancer syndrome characterized by tumors of endocrine organs including pituitary adenomas, is located on 11q13.…”
Section: Resultsmentioning
confidence: 99%
“…This technique allows gross chromosomal changes (gains and losses) and ploidy to be determined in a single experiment. These studies have Multiple transcripts examined all the major pituitary tumour subtypes; however, the number of tumours examined is limited (Tanaka et al 1997, Daniely et al 1998, Harada et al 1999, Hui et al 1999, Metzger et al 1999, Finelli et al 2000, Fan et al 2001, Rickert et al 2001, Trautmann et al 2001. Perhaps reflecting this limitation, these studies reached different conclusions with respect to gains and losses.…”
Section: Whole Genome Cytogenetic Alterationsmentioning
confidence: 98%
“…To our knowledge, only conventional comparative genomic hybridization (CGH) studies have been conducted in this tumor type [35][36][37][38][39]. Briefly, the most common chr aberrations in PAs are gains of chr 19 (16-30%), chr 12 (7-15%), chr 7 (7-27%) and chr 9 (7-15%), and losses of chr 11 (5-8%) and chr 13 (4-42%), with no significant differences among the various pathological subtypes [35][36][37][38].…”
Section: Pituitary Adenomasmentioning
confidence: 99%
“…Briefly, the most common chr aberrations in PAs are gains of chr 19 (16-30%), chr 12 (7-15%), chr 7 (7-27%) and chr 9 (7-15%), and losses of chr 11 (5-8%) and chr 13 (4-42%), with no significant differences among the various pathological subtypes [35][36][37][38]. However, it has been suggested that amplifications on chr 19 and 22q may be involved in the pathogenesis of growth hormone-secreting adenomas [36].…”
Section: Pituitary Adenomasmentioning
confidence: 99%